1990
DOI: 10.2307/1317631
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Critical Thinking and Writing through Debates: An Experimental Evaluation

Abstract: Whitewater Faced with the desire to maintain high standards of scholarship in a context of large introductory level classes and limited resources, the authors experimented with several active learning techniques designed to develop critical thinking and writing skills. The tentative conclusions drawn are that the debateformat in the context of large classes is an effective way to modify students' opinions on social issues and to teach critical thinking and writing skills. Also discussed are several ethical iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 11 publications
3
66
0
1
Order By: Relevance
“…Firstly, they had to be prepared to challenge their initial perceptions; secondly, they had to work through the opposing views and look for appropriate arguments; and thirdly, they needed to reflect upon and consolidate the arguments supporting their own perspectives in order for them to continue to believe that asylum seekers should be able to work in the UK. The critical insight and more nuanced responses from the students was in contrast to some of the debate literature which found that debates shaped learner's attitudes, often away from their original perspectives (Green & Klug, 1990;Omelicheva & Avedeyeva, 2008;Kennedy, 2009). Here the majority of students still maintained their original views, but were more tempered in their statements, and nuanced in their reasoning.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Firstly, they had to be prepared to challenge their initial perceptions; secondly, they had to work through the opposing views and look for appropriate arguments; and thirdly, they needed to reflect upon and consolidate the arguments supporting their own perspectives in order for them to continue to believe that asylum seekers should be able to work in the UK. The critical insight and more nuanced responses from the students was in contrast to some of the debate literature which found that debates shaped learner's attitudes, often away from their original perspectives (Green & Klug, 1990;Omelicheva & Avedeyeva, 2008;Kennedy, 2009). Here the majority of students still maintained their original views, but were more tempered in their statements, and nuanced in their reasoning.…”
mentioning
confidence: 72%
“…This offers the opportunity to focus upon particular perspectives of issues, but not the same level of 'thinking on your feet' which forms a central part of a debate. Learning to cope with the uncertainty offers the opportunity to develop enhanced written and/or oral communication skills; research skills; analysis, synthesis and evaluation skills; critical thinking skills; argument and persuasion skills (Green & Klug, 1990;Dundes, 2001;Kennedy, 2009). Significantly, these include the development of the higher level cognitive skills of Bloom's Taxonomy (Kennedy, 2009).…”
Section: Debates Within Teachingmentioning
confidence: 99%
See 3 more Smart Citations